The transfer of double morphologically good Day 5 blastocysts increases the risk of clinical pregnancy loss in singleton pregnancies following frozen-thawed embryo transfer - Wang, Yufeng; Wan, Qin; Lu, Xiaohui; Li, Lingjun; Wang, Huihui; Chen, Li; Dai, Xiuliang (Frontiers in Endocrinology, 2025)
BackgroundTo investigate whether double embryo transfer (DET) increases the risk of spontaneous clinical pregnancy loss (CPL) in singleton pregnancies following frozen-thawed embryo transfer (FET), compared to single embryo transfer (SET).MethodsThis retrospective cohort study included 2,448 females with singleton pregnancies (excluding vanishing twin cases) resulting from frozen-thawed single or double embryo transfers between January 2017 and September 2022. The CPL rate was the sole outcome measure. We compared CPL rates between SET and DET across three populations with increasing embryo developmental potential using binary logistic regression analysis: P1, comprising transfers of Day 3 cleavage-stage embryos; P2, comprising transfers of blastocysts; and P3, comprising transfers of top-quality blastocysts, defined as morphologically good Day 5 blastocysts.ResultsAfter adjusting for confounding factors, the comparison between SET and DET revealed the following findings: in P1, DET had a slightly higher CPL rate compared to SET [OR (95% CI): 1.18 (0.74-1.90), p=0.46]; In P2, DET showed a moderately higher CPL rate [OR (95% CI): 1.34 (0.96-1.87), p=0.08]; In P3, DET had a significantly higher CPL rate [OR (95% CI): 1.55 (1.02-2.37), p=0.04]. A combined analysis indicated that as the developmental potential of the transferred embryo increased (from P1 to P2 and further to P3), the impact of DET on CPL also increased, as reflected by the rising OR values and decreasing p-values. We proposed that in singleton pregnancies resulting from DET, the loss of a non-viable embryo at a later stage, when it has a larger cell mass, may trigger excessive intrauterine inflammation, thereby increasing the risk of CPL for the remaining full developmental potential embryo. In singleton pregnancies resulting from DET, a higher-quality embryo that fails is more likely to die at a later stage. This could explain why the impact of DET on CPL increases with the developmental potential of the embryo.ConclusionSince a significant difference in CPL between SET and DET was only observed in P3 population. Therefore, we concluded that compared to SET, the transfer of double morphologically good Day 5 blastocysts is associated with increased clinical pregnancy loss in singleton pregnancies following FET.